2003
DOI: 10.1037/0022-006x.71.3.452
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of treatment outcome from relationship variables in child and adolescent therapy: A meta-analytic review.

Abstract: Results from 23 studies examining associations between therapeutic relationship variables and treatment outcomes in child and adolescent therapy were reviewed with meta-analytic procedures. Results indicated that the overall strength of the relationship-outcome associations was modest and quite similar to results obtained with adults. This modest association was moderated by 1 substantive factor, type of patient problem, and 5 methodological factors, timing and source of relationship measurement, type and sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

45
524
8
20

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 573 publications
(597 citation statements)
references
References 71 publications
45
524
8
20
Order By: Relevance
“…Surveys have shown that clinicians who provide mental health services to child and adolescent clients highly value the therapeutic relationship (Bickman et al, 2000). The metaanalysis by Shirk and Karver (2003) also showed that therapeutic relationship variables are predictive of youth treatment outcomes. Yet, little is known about how these therapeutic relationship variables contribute to positive treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surveys have shown that clinicians who provide mental health services to child and adolescent clients highly value the therapeutic relationship (Bickman et al, 2000). The metaanalysis by Shirk and Karver (2003) also showed that therapeutic relationship variables are predictive of youth treatment outcomes. Yet, little is known about how these therapeutic relationship variables contribute to positive treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As Lambert and Barley (2002) noted, common process factors (i.e., relationship variables) reportedly account for 30% of the variance in adult treatment outcomes, above and beyond the 15% of variance accounted for by specific therapeutic techniques. Furthermore, empirical research suggests that one common factor, the therapeutic alliance, is among the most robust predictors of treatment outcomes for both adult and youth clients (Horvath & Bedi, 2002;Shirk & Karver, 2003). Recognizing the need for more research on common process factors, Division 29 of the American Psychological Association formed the Task Force on Empirically Supported Therapy Relationships to determine which relationship variables are evidencebased (Norcross, 2002).…”
mentioning
confidence: 99%
See 3 more Smart Citations